Peningkatan Hasil Belajar Peserta Didik Menggunakan Model Discovery Learning pada Pembelajaran IPAS di Kelas V SDN 09 Rantau Utara Kabupaten Labuhan Batu - Julianti, Julianti; Adrias, Adrias; Zuardi, Zuardi; Zahara, Leni (Indo-MathEdu Intellectuals Journal, 2025)
The background of this research is based on initial observations indicating that the learning outcomes of students in social studies (IPAS) need to be improved. The discovery learning model was chosen because this approach encourages students to actively construct their own knowledge through a series of steps such as stimulating interest, identifying problems, collecting data, processing data, proving, and generalizing. This study aims to improve student learning outcomes in social studies at SD Negeri 09 Rantau Utara, Labuhan Batu District, using the discovery learning model. This research employs a classroom action research method (PTK) conducted in two cycles. Data were collected through learning outcome tests, observations, and interviews. The research results show a significant increase in the learning outcomes of students after the implementation of the Discovery Learning model. The average learning outcome score increased from 69.91 in cycle I to 85.3 in cycle II. The percentage of learning mastery also showed an increase, reaching the established target. Therefore, it can be concluded that the implementation of the Discovery Learning model is effective in improving the learning outcomes of IPAS students in grade V of SD Negeri 09 Rantau Utara.